1998
DOI: 10.2108/zsj.15.139
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Positions of Insectivora in Eutheria Inferred from Mitochondrial CytochromecOxidase Subunit II Gene

Abstract: For the elucidation of the phylogenetic position of insectivora in eutheria, we have sequenced the cytochrome c oxidase subunit II (COII) gene of mitochondria for three insectivoran species [musk screw (Suncus murinus), shrew mole (Urotrichus talpoides), Japanese mole (Mogera wogura)] and analyzed these amino acid sequences with neighbor-joining (NJ) method and maximum likelihood (ML) method. NJ analysis shows polyphyly of Insectivora and Chiroptera. Assuming that each of Primates, Ferungulata, Chiroptera, Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Rouse and Robson [21] reported that the morphological features of the outer dense fiber of spermatozoa are in common between the order Insectivora and the order Chiroptera. Additionally, some molecular studies [3,18] pointed out the phylogenetic similarity between these two orders. The present finding may also reflect the fact that the order Chiroptera is phylogenetically close to the order Insectivora.…”
Section: Discussionmentioning
confidence: 99%
“…Rouse and Robson [21] reported that the morphological features of the outer dense fiber of spermatozoa are in common between the order Insectivora and the order Chiroptera. Additionally, some molecular studies [3,18] pointed out the phylogenetic similarity between these two orders. The present finding may also reflect the fact that the order Chiroptera is phylogenetically close to the order Insectivora.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas several studies have shown that Eulipotyphla is not the basal relative of Laurasiatheria, affinities have been suggested between Eulipotyphla and Carnivora based on the molecular analysis of amino acid sequences of several proteins (Miyamoto and Goodman, 1986) and morphological analysis (MacPhee and Novacek, 1993). Molecular phylogenetic studies on the mitochondrial cytochrome c oxidase subunit II gene (Onuma et al, 1998) and the nuclear interphotoreceptor retinoid binding protein gene (Stanhope et al, 1996) have suggested that the Eulipotyphla are closely related to Chiroptera. Thus, the phylogenetic position of Eulipotyphla is a matter of controversy.…”
Section: Introductionmentioning
confidence: 99%
“…When we focus on the EulipotyphlaChiroptera relationship, several molecular phylogenetic analyses are found to deal with this subject. Analyses based on the nuclear interphotoreceptor retinoid binding protein gene (Stanhope et al, 1996) and on the mitochondrial cytochrome c oxidase subunit II gene (Onuma et al, 1998) have supported the affinity between Eulipotyphla and Chiroptera, whereas analysis based on the complete mitochondrial DNA sequences did not support such an affinity (Krettek et al, 1995). However, it has been suggested that the use of hedgehog as a representative of Eulipotyphla causes such inconsistency, and the high affinity of mole and bat has been shown (Mouchaty et al, 2000).…”
mentioning
confidence: 99%
“…However, paraphyly of Eulipotyphla is inconsistent with several subsequent molecular analyses of concatenated sequences of nuclear exons and mitochondrial rRNA genes that placed a monophyletic Eulipotyphla as the most basal lineage in the Laurasiatheria (Madsen et al 2001, Matthee et al 2001, Waddell et al 2001, Kriegs et al 2006, Nishihara et al 2006). Additionally, some molecular studies (Onuma et al 1998, Mouchaty et al 2000, Narita et al 2001, Nikaido et al 2001) strongly supported a sister-group relationship between Eulipotyphla and Chiroptera named Insectiphillia (Waddell et al 2001). Thus, the position of Eulipotyphla, either as a basal clade of Laurasiatheria or within Insectiphillia, has been a matter of great controversy.…”
mentioning
confidence: 99%